A Cross Sectional Study to Estimate the Stature from Hand length in the Age Group of 18 to 25 Years in Telangana Population - K Srinivasulu; B. Shruthi Reddy; Sowmya Bhashini Popuri; T Rahul Reddy; Ram Prasanjith Reddy Bollampalli; Sudheera Polavarapu; Rishabh Chormalle (Institute of Medico-legal Publications Pvt Ltd, 2022)
A Cross sectional study on correlation of length of hand in relation to the height of an individual was conductedin medical students of Telangana region in the age group of 18 to 25yrs during the period of January 2018 toDecember 2019. A total of 150 individuals among 75 males and 75 females were taken as participants in this study.Measurement of the Body part hand length has taken as distance between the proximal wrist creases to the tip ofmiddle finger, measured by using vernier calipers. The data was statistically analyzed by using SPSS (version-25)software.The formula for linear regression for estimating the height is y = a + (b x), y = dependent variable (height). a= constant. b = independent variable coefficient. x = independent variable i.e. length of the Hand. The linearregression formula for Right hand is y = 41.25 + (6.89 x) and left hand is y = 43.9 + (6.71 x). In case of maleindividuals the formula for Right hand is y = 68.77 + (5.47 x) and for left hand is y = 63.69 + (5.70 x). In caseof female individuals the formula for Right hand is y = 59.51 + (5.72 x) and for left hand is y = 63.63 + (5.48 x),standard error was 0.3, R square of 0.7 and confidence interval was 6.17 – 7.60, the data results show the statisticalsignificance the P Value less than 0.001.Calculated stature from the equation Y=a + (b x), is close to the actual height, only ± 5cm difference was observedin most of the individuals. Height of an individual is approximately 9 times the height of the hand length. Aseparate linear regression formula for male and female is more accurate and reliable.